Youth, suicide and suicidal survival in Heine T. Bakkeid’s Uten puls (2006), Oliver Lovrenski’s da vi var yngre (2023) and Simon Stranger’s 304 dager (2021) - Moi, Ruben (Nordlit, 2024)
Why do young people commit suicide? How does young adult fiction present teenage suicide? Suicide fiction can be simplistically defined as a literary work in which suicide constitutes the life-altering event for the character(s)’ death or survival, and for the next of kin’s challenges. This article meditates upon how the young adult novels Uten puls (2006) by Heine T. Bakkeid, da vi var yngre (2023) by Oliver Lovrenski and 304 dager (2021) by Simon Stranger present suicide, survival, and the next of kin’s experience and importance. The explorations of these young adult suicide novels are predominantly literary, although they also draw upon Durkheim’s sociology in Suicide (1897), on Freud’s psychoanalytical theory, and on Camus’ philosophical classic, The Myth of Sisyphus (1942).